Réflexions et jeux d’échelles autour de la notion de « guerre civile européenne » - Romain Bonnet (Amnis)
The fashionable concept of « European Civil War » seeks to grasp the violent phenomena of socio-political radicalisations and polarisations which have been typical of the inter war period. Yet that said, those realities do not correspond to a civil war (which would imply well-defined front lines), nor are they only concerned with the interwar European context (precisely circumscribed between two World Wars, which determined the place of Europe in a world largely unified by and for it for half a Millennium). Thus, this article proposes a reflection on the capacity for articulation of the chronological and geographical scales of analysis within the concept of « European civil war ». First, we present an outline of historicisation of said concept in the current historiographical field, judged in terms of the « short XXth century », which had been so deeply and durably marked by the interwar context. Second, we insist on the still massive predominance of rural worlds in interwar Europe, and, thus, on their crucial importance as an explanative factor of the « European civil war ». This is all the more important since a relative and paradoxical historiographical silence surround said rural worlds. We conclude by comparing the concepts of « European civil war » (E. Nolte) and the « age of extremes » (E. Hobsbawm) by dealing with their explanative potentialities in terms of articulation of the geographical and chronological scales of analysis.